2022
DOI: 10.1177/14673584221093538
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model of the determinants and outcomes of workplace ostracism in the tourism industry

Abstract: This paper investigates the impact of organizational deviance and coworker envy on workplace ostracism. It also assesses the effect of workplace ostracism on knowledge hiding and turnover intent and tests the interaction role of job tension on such associations. PLS-SEM was utilized to analyze 591 responses collected from employees at Egyptian travel agencies-A. The findings articulated that ostracism was positively impacted by both organizational deviance and coworker envy. Additionally, ostracism at the work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…It can be shown that VB-SEM is a standard analytical approach that has been used in a number of research in the tourism industry. (e.g., Hassan and Soliman, 2021; Soliman et al, 2022), including the context of travel agents in Egypt (e.g., Abdelhamied and Elbaz, 2018; Al-Romeedy et al, 2020; Abou-Shouk and Soliman, 2021; Elbaz et al, 2021; Soliman and Wahba, 2019).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…It can be shown that VB-SEM is a standard analytical approach that has been used in a number of research in the tourism industry. (e.g., Hassan and Soliman, 2021; Soliman et al, 2022), including the context of travel agents in Egypt (e.g., Abdelhamied and Elbaz, 2018; Al-Romeedy et al, 2020; Abou-Shouk and Soliman, 2021; Elbaz et al, 2021; Soliman and Wahba, 2019).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…In the same context, during the literature review, past studies exploring the outcome of ostracism in the hospitality and tourism industries in terms of turnover intentions (Anasori et al, 2021;Singh and Srivastava, 2021), knowledge hiding (Soliman et al, 2023) and service recovery performance (Pas amehmeto glu et al, 2022) were observed. In addition, the previous studies based on meta-analysis and literature reviews on workplace ostracism (Ferris et al, 2015;Howard et al, 2020;Sharma and Dhar, 2021) were explored, but the research unearthing the impact of ostracism on procrastination behaviour was limited, creating a research gap.…”
Section: Introductionmentioning
confidence: 97%
“…Given the prevalence of this destructive phenomenon of ostracism, it is essential to shed light on its major causes and detrimental effects on the tourist industry, especially given the scant research that has been done on such a significant phenomenon in the industry (Sarwar et al , 2023; Soliman et al , 2023). In the current post-pandemic scenario, the unwanted outcome behaviour of an employee at the workplace, such as poor service performance, a feeling of insecurity, sabotage intention, workplace deviance or procrastination behaviour due to interpersonal issues, also needs to be addressed as a priority (Jung et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0025-1747.htm behaviour, workplace ostracism has recently received more attention from hospitality researchers (Haldorai et al, 2022;Han and Hwang, 2021;Singh and Srivastava, 2021;Soliman et al, 2022). Moreover, workplace ostracism generates various organisational and individual outcomes adversely, including in-role performance (Rabiul et al, 2023b), turnover intention (Singh and Srivastava, 2021), citizenship behaviour (Han and Hwang, 2021), recovery performance (Pas ¸amehmeto glu et al, 2022), work effort (Anjum et al, 2022), organisational climate (Dash et al, 2023), job performance, self-esteem (Kuo and Wu, 2023) and counterproductive behaviour (Liu et al, 2023;Ugwu et al, 2023;Zhao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to service-oriented behaviour, workplace ostracism has recently received more attention from hospitality researchers (Haldorai et al. , 2022; Han and Hwang, 2021; Singh and Srivastava, 2021; Soliman et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%